2020
DOI: 10.1016/j.heliyon.2020.e04856
|View full text |Cite
|
Sign up to set email alerts
|

Docking based screening and molecular dynamics simulations to identify potential selective PDE4B inhibitor

Abstract: Inhibition of phosphodiesterase 4 (PDE4) is a promising therapeutic approach for the treatment of inflammatory pulmonary disorders, i.e. asthma and chronic obstructive pulmonary disease. However, the treatment with non-selective PDE4 inhibitors is associated with side effects such as nausea and vomiting. Among the subtypes of PDE4 inhibited by these inhibitors, PDE4B is expressed in immune, inflammatory and airway smooth muscle cells, whereas, PDE4D is expressed in the area postrema and nucleus of the solitary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Our current study examines various genetically engineered rodent models to demonstrate a major role for PDE4B expressed in ECs in PH development and show that the roflumilast-mediated improvements in PH result from its inhibition of PDE4B. Roflumilast is associated with side effects that can limit patient compliance, including gastrointestinal side effects such as nausea and vomiting, and previous studies showed that PDE4D expressed in the area postrema and nucleus of the solitary tract is responsible for emetic symptoms 16 , 17 . Also, Pde4d KO mice are resistant to xylazine/ketamine-induced anesthesia, a behavior correlated with emesis in rodents 42 .…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our current study examines various genetically engineered rodent models to demonstrate a major role for PDE4B expressed in ECs in PH development and show that the roflumilast-mediated improvements in PH result from its inhibition of PDE4B. Roflumilast is associated with side effects that can limit patient compliance, including gastrointestinal side effects such as nausea and vomiting, and previous studies showed that PDE4D expressed in the area postrema and nucleus of the solitary tract is responsible for emetic symptoms 16 , 17 . Also, Pde4d KO mice are resistant to xylazine/ketamine-induced anesthesia, a behavior correlated with emesis in rodents 42 .…”
Section: Discussionmentioning
confidence: 91%
“…The PDE4 family is encoded by four different genes, PDE4A, PDE4B, PDE4C, and PDE4D, and the encoded isozymes have distinct tissue/cell expression patterns and functional roles. Their broad functions and distribution are likely to contribute to the side effects associated with pan-PDE4 inhibitor drugs; for example, the emetic side effects of pan-PDE4 inhibitors have been linked to PDE4D expression in the nervous system 16 , 17 . Therefore, identifying the PDE4 isozyme(s) that are most biologically relevant to the pathology of PH could guide the development of PDE4 isozyme-specific inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…These techniques allow for quick screening and prediction of compounds' biological activity, making them especially attractive to the pharmaceutical industry. Molecular docking is a particularly important application of these techniques in the virtual screening [ 69 , 70 ]. Automated docking tools such as HADDOCK, Z-Dock, Molecular Operating Environment (MOE), PyRx, and AutoDock have been developed for various applications.…”
Section: Methodsmentioning
confidence: 99%
“…The docked protein–ligand complex with the lowest binding energy was subjected to molecular dynamics (MD) simulations using PMEMD.CUDA in AMBER 14 package. 30 The general AMBER force field (GAFF) parameters were assigned for the ligand, and the restricted electrostatic potential (RESP) was calculated under Gaussian g09. The parameters and topologies for the protein–ligand complex were obtained by tleap, and Amber forcefield (ff14SB) was assigned to the complex.…”
Section: Methodsmentioning
confidence: 99%